2022
DOI: 10.3389/fgene.2022.962449
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the spectrum of gamma-secretase complex missense variation in the context of hidradenitis suppurativa—An in-silico study

Abstract: Hidradenitis suppurativa (HS) is a disease of the pilosebaceous unit characterized by recurrent nodules, abscesses and draining tunnels with a predilection to intertriginous skin. The pathophysiology of HS is complex. However, it is known that inflammation and hyperkeratinization at the hair follicle play crucial roles in disease manifestation. Genetic and environmental factors are considered the main drivers of these two pathophysiological processes. Despite a considerable proportion of patients having a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…In contrast to other complex traits, the contribution of noncoding or regulatory genomic variants and polygenic risk scores to HS is unknown. The GSC bears a high burden of rare deleterious variants in the gno-mAD reference data set 4 that can be associated with lateonset disease and confound variant classification. 18 Thus, rare or novel nonsynonymous variants are often classified as VUS, limiting their interpretation and clinical actionability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other complex traits, the contribution of noncoding or regulatory genomic variants and polygenic risk scores to HS is unknown. The GSC bears a high burden of rare deleterious variants in the gno-mAD reference data set 4 that can be associated with lateonset disease and confound variant classification. 18 Thus, rare or novel nonsynonymous variants are often classified as VUS, limiting their interpretation and clinical actionability.…”
Section: Discussionmentioning
confidence: 99%
“…Hidradenitis suppurativa is a heritable trait, with up to 35% of patients having a family history . Variants in genes encoding the γ secretase complex (GSC) proteins (primarily NCSTN ) are implicated in most familial HS cases that have an underlying monogenic etiology. The GSC functions in Notch regulation, which plays a pivotal role in follicular differentiation and epidermal homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“… 26 The majority of variants implicated in HS involve one of the four γ-secretase complex (GSC) genes but predominantly NCSTN. 27 …”
Section: Epidemiology Of the Hidradenitis Suppurativamentioning
confidence: 99%
“…26 The majority of variants implicated in HS involve one of the four γ-secretase complex (GSC) genes but predominantly NCSTN. 27 Besides a link to genetics, environmental factors also contribute to HS. For example, a retrospective study (n=45) demonstrated that ten patients had reported mechanical irritation before the disease started.…”
Section: Risk Factors or Determinants Of Hidradenitis Suppurativamentioning
confidence: 99%
“…This devastating disease has a significant impact on many aspects of patients’ lives [ 7 ]. The cause of hair follicle plugging is still unclear and subject to scientific debate, although immune and genetic factors, particularly variants in genes encoding ɣ secretase complex proteins ( NCSTN encoding nicastrin; PSEN1 for presenilin-1; PSENEN for presenilin enhancer; gamma-secretase subunit), hormonal fluctuations, and environmental risk factors are believed to play a role [ 8 , 9 , 10 ]. The most common sites for hidradenitis suppurativa are the main folds of the body, including the axillary and inguinal regions, the skin of the buttocks, the sub-mammary area, and the neck, waist, and inner side of the thighs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%